2012
DOI: 10.1177/216507991206000803
|View full text |Cite
|
Sign up to set email alerts
|

Burnout among Workers in a Pediatric Health Care System

Abstract: Burnout among health care workers is recognized as an organizational risk contributing to absenteeism, presenteeism, excessive turnover, or illness, and may also manifest as decreased patient satisfaction. Pediatric health care may add stressors including worried parents of ill or dying children, child custody issues, child abuse, and workplace violence. The purpose of this study was to measure burnout among workers in a regional pediatric health care system and report whether burnout in a pediatric health car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 20 publications
(33 reference statements)
0
14
1
Order By: Relevance
“…In the present study, one out of every four respondents considered themselves to be emotionally exhausted, and this prevalence was higher than another study conducted in a paediatric unit, in which 13% of professionals nursing exhibited high levels of emotional exhaustion (Jacobs et al. ). However, the emotional exhaustion reported by the respondents in the present study is lower than that reported by professionals from adult care units, as Brazilian (Panunto & Guirardello ) and international studies showed (Aiken et al.…”
Section: Discussioncontrasting
confidence: 77%
See 3 more Smart Citations
“…In the present study, one out of every four respondents considered themselves to be emotionally exhausted, and this prevalence was higher than another study conducted in a paediatric unit, in which 13% of professionals nursing exhibited high levels of emotional exhaustion (Jacobs et al. ). However, the emotional exhaustion reported by the respondents in the present study is lower than that reported by professionals from adult care units, as Brazilian (Panunto & Guirardello ) and international studies showed (Aiken et al.…”
Section: Discussioncontrasting
confidence: 77%
“…Studies conducted in paediatric care units have demonstrated the prevalence of high levels of emotional exhaustion among professionals, especially among nurses (Jacobs et al. ; Profit et al. ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In childcare units, several factors can be identified as aggravating circumstances for the risk to health: the child's vulnerability to stress, parental suffering, the multiplicity of diseases and the developmental stage (Jacobs et al . , Alves et al . ).…”
Section: Introductionmentioning
confidence: 99%